2008
DOI: 10.1152/japplphysiol.00861.2007
|View full text |Cite
|
Sign up to set email alerts
|

Targeted imaging of hypoxia-induced integrin activation in myocardium early after infarction

Abstract: The alphavbeta3-integrin is expressed in angiogenic vessels in response to hypoxia and represents a potential novel target for imaging myocardial angiogenesis. This study evaluated the feasibility of noninvasively tracking hypoxia-induced alphavbeta3-integrin activation within the myocardium as a marker of angiogenesis early after myocardial infarction. Acute myocardial infarction was produced by coronary artery occlusion in rodent and canine studies. A novel (111)In-labeled radiotracer targeted at the alphavb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…They are widely expressed by many cell types, including endothelial and smooth muscle cells (Cheresh1987; Janat et al 1992) and are upregulated in hypoxia and angiogenesis (Brooks et al 1994;Kalinowski et al 2008). Our data demonstrate high a v integrin protein expression with strong immunohistochemistry signal in intramyocardial coronary vessels.…”
Section: Discussionmentioning
confidence: 58%
“…They are widely expressed by many cell types, including endothelial and smooth muscle cells (Cheresh1987; Janat et al 1992) and are upregulated in hypoxia and angiogenesis (Brooks et al 1994;Kalinowski et al 2008). Our data demonstrate high a v integrin protein expression with strong immunohistochemistry signal in intramyocardial coronary vessels.…”
Section: Discussionmentioning
confidence: 58%
“…Imaging of α v β 3 expression in myocardial ischemia have been reported in rats and dogs, using intravenous injection of RPT748, combining a 111 In-complex with a non-peptide α v β 3 ligand [243][244]. In vivo and ex-vivo imaging of myocardial tissue showed that 111 In uptake colocalized with neoangiogenesis in ischemic areas.…”
Section: Integrin α V β 3 In Cardiovascular Diseasesmentioning
confidence: 99%
“…111 InRP748 was also successful in assessing the activation of αvβ3 revieWS integrin in myo cardium early after infarction. 60 Other researchers have reported the use of 99m Tclabeled tracers containing the RGD motif for noninvasive imaging of angiogenesis in various animal models. [61][62][63][64] The 99m Tc labeled peptide, 99m TcNC100692, has a high affinity for the αvβ3 integrins, is metabo lically stable, and has a biodistribution favorable for in vivo imaging purposes.…”
Section: Neuroreceptor Imagingmentioning
confidence: 99%